Takwa Dalam Perspektif Al-Qur’an: Analisis Integrasi Nilai Spritual Dan Sosial - Nurlaili Apriani; Achmad Abubakar; Sohrah Sohrah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
In general, every Muslim across the globe is familiar with the term taqwa, yet not all understand it comprehensively. Taqwa is frequently interpreted solely as a vertical relationship with God, whereas it also encompasses a horizontal dimension—the relationship with fellow human beings. This study aims to explore how the Qur'an integrates the vertical relationship (Habl min Allah) and the horizontal relationship (Habl min an-Nas) into a single unified concept: taqwa. The research method employed is qualitative research using a tafsir maudhu’i (thematic interpretation) approach. The results indicate that taqwa serves as an integrative moral consciousness that combines vertical devotion to God with social responsibility toward others. This synergy fosters justice, non-discrimination, and respect for human dignity, as reflected in honesty, responsibility, empathy, and noble character (akhlak). Based on this comprehensive interpretation, taqwa can be understood as a holistic principle that integrates inner piety, moral integrity, and social commitment within a single framework of values